Industrial Application Of Value Stream Mapping In Developing Best Practices For Productivity Improvement - Wan Mahmood, Wan Hasrulnizzam; Muhamad, Mohd Razali; Ramli, Mohd Irman (2007)
The purpose of this paper is to provide a review of how a manufacturing company developed the best practices for productivity improvement in production areas by using Value Stream Mapping (VSM). VSM was used to identify bottlenecks in the plant that limits the throughput and to identify wastes which included non value added activities in the constrained production areas. Results of VSM application have revealed the plant’s overall bottlenecks and means of increasing the throughput. The study findings are originated from a composites technology company which practiced lean manufacturing system and the results may not be applicable to other types of industry. VSM is considered a very useful tool for productivity improvement that it is easy to be used by plants’ management to help them identify and manage bottlenecks, and to eliminate wastes from the production system. This paper offers practical and easy-to-use productivity improvement tools to assist manufacturing managers to boost-up the productivity.